2019
DOI: 10.21273/horttech04255-18
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Phytotoxic Effects of Hydrogen Peroxide on Common Microgreen Species and Lettuce Cultivars

Abstract: Hydrogen peroxide (H2O2) is an oxidizing agent used to disinfect recirculated irrigation water during the production of organic crops under controlled environmental systems (e.g., greenhouses). To characterize the phytotoxic effects and define a concentration threshold for H2O2, three microgreen species [arugula (Brassica eruca ssp. sativa), radish (Raph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In the trials with greenhouse-grown wild rocket, a leaf toxicity of 1000 mM H 2 O 2 was evident as scattered bleaching of the leaves within 24 h after application. This result was similar to the findings of Eicher-Sodo et al [ 66 ], who observed damage on arugula leaves after daily foliar H 2 O 2 treatment for 11 days using milder H 2 O 2 concentrations compared with our study. H 2 O 2 leads to programmed cell death as a defense mechanism of the plants [ 67 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the trials with greenhouse-grown wild rocket, a leaf toxicity of 1000 mM H 2 O 2 was evident as scattered bleaching of the leaves within 24 h after application. This result was similar to the findings of Eicher-Sodo et al [ 66 ], who observed damage on arugula leaves after daily foliar H 2 O 2 treatment for 11 days using milder H 2 O 2 concentrations compared with our study. H 2 O 2 leads to programmed cell death as a defense mechanism of the plants [ 67 ].…”
Section: Discussionsupporting
confidence: 93%
“…At the lower treatment of H 2 O 2 , the conventionally fertilized plants had somewhat stunted growth (Figure 3a,b has the potential to indiscriminately damage healthy living root tissue, consequently reducing the fresh weight of lettuce heads in higher doses. Root damage may be the result of this phytotoxicity [17,[29][30][31]. However, when H 2 O 2 at 37.5 mg/L was added to organic fertilizer, this treatment performed as well as conventional fertilizer without H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…As such, H2O2 has the potential to indiscriminately damage healthy living root tissue, consequently reducing fresh weight of lettuce heads in higher doses. Root damage may be the result of this phytotoxicity [24,25,26]. However, when H2O2 at 37.5 mg/L was added to organic fertilizer the organic fertilizer performed as well as conventional fertilizer without H2O2.…”
Section: Discussionmentioning
confidence: 99%